The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/aisy.202300399
|View full text |Cite
|
Sign up to set email alerts
|

Binary‐Stochasticity‐Enabled Highly Efficient Neuromorphic Deep Learning Achieves Better‐than‐Software Accuracy

Yang Li,
Wei Wang,
Ming Wang
et al.

Abstract: In this work, the requirement of using high‐precision (HP) signals is lifted and the circuits for implementing deep learning algorithms in memristor‐based hardware are simplified. The use of HP signals is required by the backpropagation learning algorithm since the gradient descent learning rule relies on the chain product of partial derivatives. However, it is both challenging and biologically implausible to implement such an HP algorithm in noisy and analog memristor‐based hardware systems. Herein, it is dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…It is further found that the low significant weights are not necessary to participate in the information forwarding and error backpropagation processes of the neural network [51,[62][63][64]. Thus, the gradient of the loss to the weight could be accumulated in a separate array outside of the crossbar of memristive devices, as shown in figure 6(f).…”
Section: Periodical Carrymentioning
confidence: 99%
“…It is further found that the low significant weights are not necessary to participate in the information forwarding and error backpropagation processes of the neural network [51,[62][63][64]. Thus, the gradient of the loss to the weight could be accumulated in a separate array outside of the crossbar of memristive devices, as shown in figure 6(f).…”
Section: Periodical Carrymentioning
confidence: 99%